Campylobacter fetus ssp. jejuni, Aeromonas hydrophila, bacterias helicoidales y coronavirus en intestino murino - Hernández, Francisco (1985)
Intestinal contents of 28 laboratory-bred white miee and 6 wild-caught rats were extracted and observed with phase-contrast and transmission electron microscopy; cultures were made in Butzler agar and aeromones, incubated in microaerobiosis, at 37°C for 5 days. In three mice and two rats, helicoidal bacteria were observed, with 8 to 11 periplasmic fibers and terminal branches of 8 to 11 structures, similar to flagella... In one of the rats, coronavirus-like particles were observed. Campylobacter fetus ssp. jejuni was isolated in cultures from two mice and Aeromonas hydrophila from two rats.